2021
DOI: 10.1186/s40663-021-00319-7
|View full text |Cite
|
Sign up to set email alerts
|

C:N:P stoichiometry as an indicator of Histosol drainage in lowland and mountain forest ecosystems

Abstract: Background Peatlands form one of the largest carbon pools in the terrestrial ecosystems, representing approximately one-third of the world’s soil carbon. The aim of this study was to evaluate C:N:P stoichiometry as an indicator of changes initialized by dehydration in Histosols of varied origins. Four types of Histosols from lowland and mountain areas were investigated: fibric Histosols, hemic Histosols, sapric Histosols and Histosols drainic. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous studies showed that the leaf of plants is most sensitive to environmental changes, while ecological stoichiometry in leaves can reflect nutrient accumulation and limitation in the ecosystem [36]. In addition, the ratio of C to N or P in a plant can directly indicate the plant utilization efficiency of N or P and is negatively associated with plant growth rate [37]. The leaf stoichiometry ratio was usually applied to identify nutrient restriction during plant growth [38].…”
Section: Effects Of Amf and Re-vegetation Types On Plant Stoichiometr...mentioning
confidence: 99%
“…Previous studies showed that the leaf of plants is most sensitive to environmental changes, while ecological stoichiometry in leaves can reflect nutrient accumulation and limitation in the ecosystem [36]. In addition, the ratio of C to N or P in a plant can directly indicate the plant utilization efficiency of N or P and is negatively associated with plant growth rate [37]. The leaf stoichiometry ratio was usually applied to identify nutrient restriction during plant growth [38].…”
Section: Effects Of Amf and Re-vegetation Types On Plant Stoichiometr...mentioning
confidence: 99%
“…High emissions of N 2 O in drained peatlands are associated with nitrogen-rich organic matter, with C:N ratios lower than 30 (Klemedtsson et al, 2005;Liimatainen et al, 2018). Drainage and afforestation of peatlands tends to generate relative N enrichment, decreasing C:N ratios through peat degradation and increasing N mineralization (Krüger et al, 2015;Lasota and Błońska, 2021). Moreover, drained peatlands tend to have higher bulk density and lower porosity than pristine peatlands, which can lead to rapid saturation after rain, causing N 2 O pulses due denitrification associated with temporary anoxic conditions and high NO 3 − availability (Reay et al, 2004;Cui et al, 2016;Liu et al, 2019).…”
Section: Carbon Mineralization Pathwaysmentioning
confidence: 99%